Polypharmacy, drug–drug interactions, and potentially inappropriate medications among older adults: a cross-sectional study in Northeast Ethiopia - Bedilu Linger Endalifer; Mekuanint Terefe Kassa; Yenesew Wudu Ejigu; Abyou Seyfu Ambaye (Frontiers in Public Health)
BackgroundThe global older adult population is expected to increase from 524 million in 2010 to 1.5 billion by 2050, mainly in developing countries. Age-related diseases, comorbidities, and polypharmacy make appropriate prescribing crucial. This study aimed to assess the prevalence of polypharmacy, drug–drug interaction, and potentially inappropriate medication use and its factors in an Ethiopian hospital.MethodsA facility-based cross-sectional study on 236 patients aged 65 and above at Dessie Comprehensive Specialized Hospital (Jan 2022–Apr 2023) used the 2023 Beers Criteria and START/STOP V.3 to identify potentially inappropriate medications. Polypharmacy and potential drug–drug interactions were assessed using Micromedex®, with descriptive statistics and binary logistic regression performed in SPSS version 26.ResultOf the 236 patients in this study, 94 (39.8, 95% CI: 35.7–44.5%) were prescribed at least one potentially inappropriate medication per the STOPP/START criteria, with 81 (34.3%) identified by STOPP and 13 (5.5%) by START. According to the Beers Criteria, 108 patients (45.7, 95% CI: 40.1–51.0%) received at least one potentially inappropriate medication. Polypharmacy was observed in 80 patients (33.9, 95% CI: 29.1–38.5%), and potential drug–drug interactions were identified in 111 patients (47.0%). Being female (AOR: 2.93), age ≥75 (AOR: 1.52), and polypharmacy (AOR: 3.20) were linked to potentially inappropriate medication use per Beers Criteria. Age 70–74 (AOR: 2.30) and polypharmacy (AOR: 3.10) were also associated per STOPP/START criteria.ConclusionPolypharmacy, drug–drug interactions, and potentially inappropriate medications are common among older Ethiopian patients, with age, sex, and polypharmacy as contributing factors. Future studies are needed to assess the health and economic impacts of potentially inappropriate medications use.